Implementación de un sistema de gestión de inventarios y mantenimiento de equipos informáticos mediante la metodología scrum, en los laboratorios de la carrera de ingeniería en informática y sistemas computacionales de la Universidad Técnica de Cotopaxi durante el periodo 2014-2015 - Molina Robalino, Marcia Magdalena (2015)
This research implements a system for management and inventory equipment and control, same that was developed for laboratories and Computer Systems at the Technical University of Cotopaxi. This system will optimize time and resources that can look at computer equipment and inventory reports issued, being very helpful for a better performance in the major laboratories. For the development of this system platform used. Net since worked on Visual Basic.Net and MySQL. To implement the system was based on the development of Scrum that is agile as methodology for software development and can introduce functional changes or priority at the start of each new iteration problem....